(untitled) (International Journal of Engineering and Computer Science, 2015)
This paper deals with an experimental study of an inexpensive Concrete Photovoltaic Thermal Collector (PV/T) total aperture area of 0.36 m2 , used for the simultaneous production of heat and electricity. The Concrete PV/T is characterised by a thin cement concrete slab which performs the function of collecting, absorbing and storing of the solar thermal energy. Above the concrete slab PV cells were pasted .Inside the concrete absorber PVC pipe , copper pipe and Brass pipe are embedded .Outdoor experiments were carried out under varied environmental conditions for several days during two consecutive months (from April to May 2015). The experiments were carried out by measuring the climatic variables, temperatures in different parts of the collectors, and mass flow rates of water, during the test days. Based on these measurements, the behaviour of the systems was analysed. A detailed analysis was carried out for evaluating the thermal performance of the Concrete PV/T under given operating conditions. The results obtained from the Concrete PV/T system were compared with the results obtained from a Conventional Solar PV/T system composed of a flat-plate collector (with a total aperture area of 1m2 ) tested at the same time.